Association of Paternal Workplace and Community Social Capital With Paternal Postnatal Depression and Anxiety: A Prospective Study - Doi, Satomi; Isumi, Aya; Fujiwara, Takeo (Frontiers in Psychiatry, 2022)
Objective The aim of this study is to examine the association between workplace and community social capital and fathers' postpartum depression and anxiety at 3 months after delivery in Japan. Methods Fathers who had babies delivered in two obstetric clinics in Tokyo, Japan were recruited to take part in the study (response rate = 76.2%). Participants completed questionnaires measuring workplace and community social capital, depression, and anxiety at 1 week and a follow-up at 3 months post-delivery (N = 398). Multiple linear regression analyses were performed with multiple imputation for missing data (at most, N = 60, 15.1%). Results Community social capital was inversely associated with both depressive symptoms (β = −0.21, 95%CI = −0.33 to −0.08) and anxiety (β = −0.38, 95%CI = −0.66 to −0.11) at 3 months, after adjusting for covariates. No association was found between workplace social capital and depressive symptoms and anxiety. Conclusion Paternal community social capital, but not workplace social capital, was shown to be a preventive factor for paternal depression and anxiety up to 3 months post-delivery. To prevent paternal mental health problems during the postpartum period, an intervention to promote paternal community, rather than workplace, social capital may be warranted.